Room-Temperature Lasing in Self-Assembled Micro-Rings of CdSe/ZnS Quantum Dots - Xiaoyu Wang; Zelei Chen; Haibin Zhao; Jun Wang (Photonics)
Colloidal quantum dots (QDs) provide an ideal platform for the development of integrated optoelectronic devices due to their excellent solution processability and size-tunable optical properties. In this paper, we investigate the self-assembly process of QD micro-rings based on the solution patterning method and the lasing phenomenon in the micro-rings. The characterization of the QD micro-rings demonstrates that they possess a high-quality morphological structure and excellent optical properties. The photoluminescence spectra of the QD micro-rings with different pump fluences are studied, and photon lasing with a narrow linewidth (0.3 nm) is found to have been achieved in the micro-rings above the threshold (<semantics>23 μJ cm−2</semantics>). The high coherence of the lasing in the QD micro-rings is revealed by angle-resolved photoluminescence (ARPL) spectra at room temperature. Moreover, the interference pattern of the coherent lasing obtained with Young’s double-slit interference method based on the far-field Fourier optical system in the ARPL spectrum reflects the distribution of the optical field in the QD micro-rings. Our research on the self-assembly of colloidal QDs and the lasing of QD micro-rings is expected to further promote the development of on-chip integrated QD optoelectronic devices.